2020
DOI: 10.21203/rs.3.rs-132099/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High proportion of caesarean section at a rural hospital in south western Uganda: A cross sectional study

Abstract: Background: Globally, overall prevalence of caesarean section (CS) is estimated at 18.6%, with 27% in high-income countries and 6% in low- and middle-income countries. There is an increase in trends of CS in Uganda from 8.5% in 2012 to 11% in 2016. There have been no studies done to account for the high rates of CS in a rural hospital in Uganda. This study determined the proportion and factors associated with CS delivery at a rural hospital in south western Uganda.Methods: This was a cross sectional study of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…There are higher rates of CS deliveries in south western Uganda than the national CS rates & WHO recommended rates. Available data from 286 health facilities in Uganda representing 509,206 births and 71% of facilities performing caesarean delivery (CD) revealed that the overall CD rate is 17.9% ranging from 0.08% to 78% [6]. Most CDs are performed in General Hospitals (50.4%) and Regional Referral Hospitals (RRHs) (24.5%) while Heath Centre IVs and Private Not For Profit (PNFP) facilities account for only 18.5%) and 6.7% of the CDs respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There are higher rates of CS deliveries in south western Uganda than the national CS rates & WHO recommended rates. Available data from 286 health facilities in Uganda representing 509,206 births and 71% of facilities performing caesarean delivery (CD) revealed that the overall CD rate is 17.9% ranging from 0.08% to 78% [6]. Most CDs are performed in General Hospitals (50.4%) and Regional Referral Hospitals (RRHs) (24.5%) while Heath Centre IVs and Private Not For Profit (PNFP) facilities account for only 18.5%) and 6.7% of the CDs respectively.…”
Section: Introductionmentioning
confidence: 99%